Improvising Early Music: The History of Musical Improvisation from the Late Middle Ages to the Early Baroque - Moelants, Dirk; Wegman, Rob C.; Menke, Johannes; Schubert, Peter (Leuven Leuven University Press, 2014)
Studying improvised music is always a challenge, due to its volatility and unpredictability. But what about studying musical improvisation from before the age of sound recordings? In this book three experts give their view on aspects of musical improvisation in the late medieval, renaissance, and early baroque periods. Historical sources show us how improvisation was an integral part of music education and how closely improvisation and composition were linked. This gives new insights into the way music was played in its original historical context and a new way to look at written scores from the past.Improvising Early Music will appeal to anyone interested in the historical background of our written musical heritage, and to musicians who want to gain a deeper insight in the way this music was created.ContributorsJohannes Menke (Schola Cantorum Basiliensis, Basel), Peter Schubert (Schulich School of Music, McGill University, Montreal), Rob C. Wegman (Princeton University)
Keywords: Middle Ages (500-1400); Renaissance (1400-1600); 17th Century (1601-1700); Early music; Improvisation